The use of misoprostol as a prevention for post-partum hemorrhage after cesarean ection - Thomas Yohan Junardi; Yessica Mishellin Awaloei (Institute of Computer Science (IOCS), 2023)
This systematic literature review was organized to evaluate a potential uterotonic agent named misoprostol, as the choice to prevent and manage PPH. Compiled this systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guide to analyze the role and efficacy of misoprostol for the prevention of post-partum bleeding after cesarean section. A literature search was conducted on five databases, namely MEDLINE, The Cochrane Library, Wiley Sciencedirect, and Google Scholar based on the PRISMA guide lists. Quality and risk assessments were carried out through the Cochrane Risk of Bias Tool 2.0 checklist and any disagreements among the authors that were resolved by discussion. Literature search and selection resulted in ten studies that met the inclusion and exclusion criteria. Misoprostol has been shown to reduce post-caesarean bleeding compared to other agents. Evaluation then was carried out through decreased hemoglobin, hematocrit, visual evaluation of bleeding, as well as the need for additional blood transfusions and uterotonic agents. The high incidence of PPH in caesarean section and the magnitude of the accompanying risks indicate the importance of a form of PPH prevention to improve the safety of mother and baby. The results obtained from this study showed the safety and effectiveness of misoprostol in the treatment of PPH after caesarean section.